Feasibility Analysis of Laying Chicken Breedering Businesses in Marketing, Financial and Environmental Aspects - Hardianawati (MultiTech Publisher, 2023)
This type of research is qualitative research. The method used in this research is a combination of qualitative methods on marketing and environmental aspects and then quantitative methods on financial aspects. The qualitative research method is an interview process regarding the understanding of a matter to obtain data, information, texts of the views of respondents using various methodologies on a problem. The quantitative method is data retrieval based on the numerical calculation data collected and then added up. This study aims to obtain data and information as well as responses when the research is taking place with what is in the field. This writing method uses a centralized interview method by obtaining information by means of face-to-face or online question and answer between the researcher (as an interviewer with or without using an interview guide) and the subject under study and using observation or direct observation by looking at the cage situation, marketing and his finances. The results of the study show that (1) based on the marketing aspect, looking at the market, demand conditions are stable and continue to increase every year due to the egg sales strategy so that this business is feasible to run for 3 years. (2) based on the financial aspect, it can be seen that from 2020-2023 it has increased even though the number of chickens has decreased because the cost of buying seeds was not calculated in 2021, while in 2023 there was an addition of seeds so that it can be seen that profits have increased from 2020-2021. (3) based on environmental aspects it is very conducive, it is kept clean and healthy, so there are no problems in the environment because it has been anticipated by the farm so it is feasible to run. The conclusion of the study shows that marketing, financial and environmental aspects in the feasibility analysis of a small-scale laying hen business are feasible to run because they have fulfilled all the aspects carried out.